Just in Time on Mechanical and Electrical Implementation in Leedon Hotel Surabaya - Felicia Nuciferani; Diah Listyaningsih; M. Ferdaus Noor Aulady; M.Irsadul Ibad Adde Santoso (Institut Teknologi Adhi Tama Surabaya, 2022)
Mechanical electrical and plumbing (MEP) job is a job in construction project and the implementation is conducted after the workers conduct structural work. The use of materials has an important part from project total cost because waste will be happened if it is used uncontrollable. The aim of this study was identifying JIT application to electrical work in Leedon Hotel Surabaya. The condition before the researcher implemented JIT in Leedon Hotel project, it was identified waste caused by design change, lack of coordination between project and Head Office, and materials availability with excess material stocks. The limited size of the warehouse as MEP materials storage made the material storage not optimal and it had potential to be waste. Applying just in time concept had a focus on waste elimination by planning - needs - use in the field based on the application of JIT method in the Leedon Hotel project. Limited warehouse conditions could still carry out material control without using excess material inventory which had an impact on minimizing the emergence of waste.